Air pollution in China: Status and spatiotemporal variations - Song, Congbo; Wu, Lin; Xie, Yaochen; He, Jianjun; Chen, Xi; Wang, Ting; Lin, Yingchao; Jin, Taosheng; Wang, Anxu; Liu, Yan; Dai, Qili; Liu, Baoshuang; et al. (Environmental pollution (1987), 2017)
In recent years, China has experienced severe and persistent air pollution associated with rapid urbanization and climate change. Three years' time series (January 2014 to December 2016) concentrations data of air pollutants including particulate matter (PM2.5 and PM10) and gaseous pollutants (SO2, NO2, CO, and O3) from over 1300 national air quality monitoring sites were studied to understand the severity of China's air pollution. In 2014 (2015, 2016), annual population-weighted-average (PWA) values in China were 65.8 (55.0, 50.7) μg m−3 for PM2.5, 107.8 (91.1, 85.7) μg m−3 for PM10, 54.8 (56.2, 57.2) μg m−3 for O3_8 h, 39.6 (33.3, 33.4) μg m−3 for NO2, 34.1 (26, 21.9) μg m−3 for SO2, 1.2 (1.1, 1.1) mg m−3 for CO, and 0.60 (0.59, 0.58) for PM2.5/PM10, respectively. In 2014 (2015, 2016), 7% (14%, 19%), 17% (27%, 34%), 51% (67%, 70%) and 88% (97%, 98%) of the population in China lived in areas that meet the level of annual PM2.5, PM10, NO2, and SO2 standard metrics from Chinese Ambient Air Quality Standards-Grade II. The annual PWA concentrations of PM2.5, PM10, O3_8 h, NO2, SO2, CO in the Northern China are about 40.4%, 58.9%, 5.9%, 24.6%, 96.7%, and 38.1% higher than those in Southern China, respectively. Though the air quality has been improving recent years, PM2.5 pollution in wintertime is worsening, especially in the Northern China. The complex air pollution caused by PM and O3 (the third frequent major pollutant) is an emerging problem that threatens the public health, especially in Chinese mega-city clusters. NOx controls were more beneficial than SO2 controls for improvement of annual PM air quality in the northern China, central, and southwest regions. Future epidemiologic studies are urgently required to estimate the health impacts associated with multi-pollutants exposure, and revise more scientific air quality index standards. [Display omitted] •Air pollution in China were characterized with three-year observed data.•Population-weighted-average concentrations in provinces, mega-city clusters and regions were calculated.•The complex air pollution caused by PM and O3 is an emerging problem in Chinese mega-city clusters.•Spatial distributions of annual average air pollutants in China were conducted.